Damage assessment of RC columns under the combined effects of contact explosion and axial loads by experimental and numerical investigations. (1st March 2022) - Mejía, Nestor; Peralta, Ricardo; Tapia, Rodrigo; Durán, Ricardo; Sarango, Andrés
Abstract: Understanding physical phenomena such as blast shock waves produced by controlled explosions is useful for problem solving in military and civil fields. The current study analyses the damage response of reinforced concrete (RC) columns exposed to contact explosion effects through experimental trials and numerical simulations and is divided into two sections: (a) experimental studies to perform and measure the damage of columns and (b) numerical studies to define the minimum quantity of pentolite 50/50 needed to collapse different RC column designs. Validation studies proved that the model was reasonably accurate. Relevant findings include the following: (a) the damage process until collapse presents a sequence in which (1) the concrete cover is fragmented, (2) the transverse bars suffer shear, (3) the longitudinal bars buckle, and (4) the concrete core is partially and fully fragmented; (b) in the case of detonations that exceed 500 g of pentolita, the type of transverse reinforcement arrangement in the RC column has significance on the final damage; and (c) the axial load increases the blast strength of the column and improves the concrete core confinement. Highlights: The objective is to get the minimum amount of explosive to collapse an RC column. Type of arrangement of transverse bars has importance for charges less than 500 g. Axial load has a direct effect on the confinement of the concrete core. Fragmentation of concrete, shear and buckle of bars defines the damage process.